2017
DOI: 10.1002/jmv.24954
|View full text |Cite
|
Sign up to set email alerts
|

Significant improvement of glycemic control in diabetic patients with HCV infection responding to direct‐acting antiviral agents

Abstract: Many studies showed insulin resistance amelioration in HCV-patients achieving Sustained Virologic Response (SVR) but results on glycemic control in diabetic patients are unclear. This study aimed to assess fasting glucose (FG) and glycated hemoglobin (HbA1c) values before and after therapy with direct-acting antivirals (DAAs) in HCV-patients with type 2 diabetes mellitus (T2DM). Of the 122 consecutively recruited patients with chronic hepatitis C and T2DM, 110 patients were treated with DAAs and 12 remained un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
85
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 45 publications
15
85
0
1
Order By: Relevance
“…An Italian study [10] aimed at the evaluation of fasting glucose and glycated hemoglobin values before and after DAA therapy in HCV patients with T2DM confirms the results of the previous study by strengthening the close link between HCV and diabetes. SVR induced a significant improvement in glycemic control, despite a significant weight gain and in 20.7% of SVR patients caused in a reduction or discontinuation of antidiabetic therapy [10] Similar data have been reported in a large Egyptian study comprising HCV genotype 4-infected patients treated with DAAs [11].…”
supporting
confidence: 80%
See 2 more Smart Citations
“…An Italian study [10] aimed at the evaluation of fasting glucose and glycated hemoglobin values before and after DAA therapy in HCV patients with T2DM confirms the results of the previous study by strengthening the close link between HCV and diabetes. SVR induced a significant improvement in glycemic control, despite a significant weight gain and in 20.7% of SVR patients caused in a reduction or discontinuation of antidiabetic therapy [10] Similar data have been reported in a large Egyptian study comprising HCV genotype 4-infected patients treated with DAAs [11].…”
supporting
confidence: 80%
“…SVR induced a significant improvement in glycemic control, despite a significant weight gain and in 20.7% of SVR patients caused in a reduction or discontinuation of antidiabetic therapy [10] Similar data have been reported in a large Egyptian study comprising HCV genotype 4-infected patients treated with DAAs [11]. Patients with improved glycemic control needed a reduction in antidiabetic drugs and insulin dose; the family history of diabetes, the presence of Child B cirrhosis, and the duration of diabetes were associated with non-improvement in glycemic control.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…HCV co-infection is associated with peripheral insulin resistance and poor glucose control in diabetes (44). Current pharmacotherapy for HCV using Sofosbuvir and Velpatasvir as shown high rates of virus eradication (45) and improved glucose control (46, 47). Therefore, people with HCV co-infection should be offered access to HCV eradication.…”
Section: Discussionmentioning
confidence: 99%
“…The HbA1c level fell shortly after LDV/SOF. The results in this study revealed a decline of HbA1c in both DM and non‐DM patients following the SVR, indicating that better sugar control may be a favorable result of successful DAA treatment in CHC patients . However, parameters associated with insulin, insulin resistance, and beta‐cell function remained unchanged in this study.…”
Section: Discussionmentioning
confidence: 53%